Identification of Partial Discharge Phenomena in Glass Insulator Testing Using HFCT - Syofyan Anwar Syahputra; Muhammad Fadlan Siregar; Muhammad Ikhwan Fahmi; Mhd Fahmi Syawali Rizki; Ahmad Faisal (JET (Journal of Electrical Technology), 2026)
Insulators are vital components in electrical power transmission systems, yet they are susceptible to degradation caused by electrical and environmental stresses. This study aims to analyze Partial Discharge (PD) characteristics in glass and porcelain insulators as an early indicator of insulation failure. Experimental testing involved a step-wise increase in AC voltage from 5 kV to 20 kV, alongside simulations of extreme conditions using exposure to a flame to trigger flashover phenomena. Discharge activity was detected using a PMDT PDetector instrument in accordance with the IEC 60270 standard. The results indicate that within the 5–15 kV range, the insulators exhibited stable performance with PD magnitudes below 20 dB. However, at 20 kV, a significant anomaly was observed in the glass insulator, characterized by a magnitude spike reaching 174 dB across the 360° phase, signaling a transition toward total failure. Phase-Resolved Partial Discharge (PRPD) pattern analysis demonstrated that thermal stress drastically lowers the air breakdown voltage threshold near the insulator surface. The study concludes that high-frequency detection methods are highly effective for the non-intrusive monitoring of insulation conditions, thereby helping to prevent catastrophic failures in electric power systems.